-(p-3)=-3(1+p)

Simple and best practice solution for -(p-3)=-3(1+p) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(p-3)=-3(1+p) equation:


Simplifying
-1(p + -3) = -3(1 + p)

Reorder the terms:
-1(-3 + p) = -3(1 + p)
(-3 * -1 + p * -1) = -3(1 + p)
(3 + -1p) = -3(1 + p)
3 + -1p = (1 * -3 + p * -3)
3 + -1p = (-3 + -3p)

Solving
3 + -1p = -3 + -3p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '3p' to each side of the equation.
3 + -1p + 3p = -3 + -3p + 3p

Combine like terms: -1p + 3p = 2p
3 + 2p = -3 + -3p + 3p

Combine like terms: -3p + 3p = 0
3 + 2p = -3 + 0
3 + 2p = -3

Add '-3' to each side of the equation.
3 + -3 + 2p = -3 + -3

Combine like terms: 3 + -3 = 0
0 + 2p = -3 + -3
2p = -3 + -3

Combine like terms: -3 + -3 = -6
2p = -6

Divide each side by '2'.
p = -3

Simplifying
p = -3

See similar equations:

| -6(-6-6k)-3k=16+7k | | 19=9r-8 | | 15.6b+0.03=10.35+16.4b | | 35=9r-10 | | 7/10x=332 | | -7/6-(-3/4) | | -7/6--3/4 | | 19f=15f-20 | | -11r=-33 | | -5x+6x+15-3x=-3 | | 200x+7000000=170x+8200000 | | -11r=-32 | | x7/10=332 | | 5h+17h-19=20h+11 | | J+19=28 | | -13s=14-15s | | 5x-4+7x-64+120+6x-8+4x+15+3x+31+135=900 | | 100k=100 | | 11=-1+3s | | Y+18=28 | | 10r=-60 | | 10-6n=n-4 | | 113-(5x+16)=5(x+4)+x | | 3(2z+7)-2(2x-1)=17 | | z/6-7=-4 | | 5(7k-3)+3=31-81k | | 2r-18=10+4r | | S-19=24 | | 2x-15=6x+17 | | (x^3-4x^2-12x)=0 | | 11(y+5)=77 | | 12x=x^2+35 |

Equations solver categories